Pengaruh Presepsi Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Restaurant Greyhound Summarecon Bekasi - Muhammad Fathur Rachman; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2023)
This study aims to analyze the simultaneous or partial influence between price perception variables (X1), product quality (X2) and service quality (X3) on customer satisfaction variables (Y). In this study, 100 respondents were collected using the purposive sampling method to conduct validity and reliability tests. To find out whether there is a partial or simultaneous influence, . The results showed that three independent variables had a simultaneous influence on the dependent variable: price perception, product quality and service quality. Partially, there are 3 independent variables that affect the dependent variable, namely price perception with a GIS value of 0.000 < 0.05, product quality with a GIS value of 0.000 < 0.05, service quality with a GIS value of 0.005 < 0.05 on customer satisfaction, and simultaneously stated significantly with a value of 0.000 < 0.05.